Experimental investigation of flow and heat transfer characteristics in double-laminated sintered woven wire mesh. (25th February 2016) - Ma, Jiandong; Lv, Pin; Luo, Xiang; Liu, Yangpeng; Li, Haiwang; Wen, Jie
Highlights: The double-laminated porous media have a strong potential for engineering application. Average porosity of wire mesh has a great influence on flow and heat transfer behaviors. Air-injected direction affects heat transfer behaviors but not flow behaviors. Abstract: Porosity is one of the major parameters of the porous media. Flow and heat transfer characteristics of double-laminated sintered woven mesh with inhomogeneous porosity were investigated experimentally. Each test piece was made up of two parts which have same wire diameter and thickness but different porosities. All experiments were performed with compressed air and the defined inlet Reynolds numbers changed approximately from 10 to 65. The specimens were heated electrically and the surface temperatures of test pieces were measured with an infrared camera. The mass flow rates and pressure drop between inlet and outlet were measured to analyze the flow behavior. The Nusselt numbers were obtained with the average wall temperature to analyze the heat transfer characteristics. The experimental results showed that different porosity combinations affect the above parameters clearly. The permeability increases with the increase in average porosity, while the inertia coefficient had an opposite tendency. Friction factors decrease with the increase in Reynolds number and Nusselt numbers increase with the increase in Reynolds number. In addition, the Nusselt numbers were different under different air flow directions.